Sweating bullets: Heat, high-stakes evaluations, and the role of incentives - Martínez, Jose María; Zuluaga, Victor; Buritica, Alexander (Springer, 2025)
We study the effect of temperature on students' performance and how changes in the incentives to study alter this impact in the context of high-school exit exams in Colombia. We show that temperature increases have a negative impact on exam scores, particularly among urban students. Conversely, rural students exhibit slightly positive effects. Leveraging time-use data, we find evidence of individuals in rural areas responding to increases in temperature by reallocating time towards off-farm activities, which are human capital intensive. Additionally, the announcement of a national scholarship program, which introduced exogenous variation in exam stakes, reveals that heightened student effort exacerbates the temperature's impact on scores. In particular, an interquartile change in the exposure to this program increases the impact of temperature on exam scores by 11.9%. This underscores the intricate relationship between incentive-based policies and the challenge of rising temperatures. As global temperatures continue to rise, understanding this dynamic is crucial for informing effective educational policy.